Integrated analysis of disulfidptosis-related genes SLC7A11, SLC3A2, RPN1 and NCKAP1 across cancers - Zequn Zheng; Yongfei Song (Discover Oncology)
Abstract Disulfidptosis, a newly identified form of regulated cell death associated with disruption of disulfide bond formation in the endoplasmic reticulum, involves the dysregulation of disulfidptosis-related genes (DRGs) that may contribute to cancer development and progression. However, the molecular mechanisms and clinical implications of DRGs in different cancer types remain poorly characterized. Therefore, in this comprehensive study, we investigated the expression, prognostic value, and functional roles of four recently identified DRGs (SLC7A11, SLC3A2, RPN1, and NCKAP1) across various cancers. Especially, in clinical samples of glioblastoma, we found that RPN1 was significantly correlated with patient survival. Through mutation landscape analysis, we identified diverse missense mutations in these DRGs, with NCKAP1 exhibiting the highest mutation frequency (5.9% in skin cutaneous melanoma). Additionally, we observed positive correlations between these DRGs and tumor stemness (DNAss DNA stemness score and RNAss RNA stemness score) as well as RNA modifications, particularly m6A modification, in several cancer types. Furthermore, high expression of SLC7A11, RPN1, and NCKAP1 was positively associated with infiltration of T-helper type 2 (Th2) cells in various cancers, while high expression of SLC7A11, SLC3A2, and RPN1 correlated with tumor mutational burden (TMB) in 10, 4, and 8 tumor types, respectively. Utilizing a protein–protein interaction network, we identified the RHO GTPases Activate WASPs and WAVEs pathway as significantly enriched, suggesting the involvement of these DRGs in cancer-related signaling pathways. Collectively, our findings provide novel insights into the molecular mechanisms and clinical implications of DRGs in pan-cancer, highlighting their potential as biomarkers and therapeutic targets for cancer treatment.